The Impact of Work Environment and Teacher Attributes on Teacher Job Satisfaction - Hsiang-Wei Ker; Ying-Haur Lee; Shu-Meei Ho (Educational Process: International Journal)
Background/purpose – Teachers play a critical role in student learning processes and in their academic success, and as such their job satisfaction directly impacts upon their teaching efficacy and lecture quality. In light of the importance of job satisfaction in educational practice, this study investigates the impact of work environment factors and personal attributes on teachers’ job satisfaction.